KELAYAKAN INVESTASI INSTALASI SEA WATER REVERSE OSMOSIS (SWRO) DI KAWASAN WISATA PANTAI KENJERAN SURABAYA - Lokajaya, I Nyoman (Heuristic, 2016)
To make Kenjeran coastal areas as the mainstay tourism Surabaya municipaladministration, provision of clean water is one of the means that must be provided.Construction of sea water purification unit with sea water reverse osmosis method isone solution that can be done. This study aims to assess the feasibility of building awater purifier sea with sea water reverse osmosis method. Finally found that for aninterval of 15 years at an average rate of visitor arrivals tourist attraction as much as7,935 people / day needed clean water supply as much as 257.09 m3 / day, equivalent to10.71 m3 / hour. Average investment value of Rp. 5.5 billion with 19:38% IRR ratemuch higher than bank interest, which is 10%. Break Even Point investment occurred inyear 7 in 2023. Keywords: investment feasibility, Sea Water Reverse Osmosis, coastel tourism area